2024
DOI: 10.1029/2023jd039427
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Cloud Feedback Components in Observations and Their Representation in Climate Models

Li‐Wei Chao,
Mark D. Zelinka,
Andrew E. Dessler

Abstract: This study quantifies the contribution of individual cloud feedbacks to the total short‐term cloud feedback in satellite observations over the period 2002–2014 and evaluates how they are represented in climate models. The observed positive total cloud feedback is primarily due to positive high‐cloud altitude, extratropical high‐ and low‐cloud optical depth, and land cloud amount feedbacks partially offset by negative tropical marine low‐cloud feedback. Seventeen models from the Atmosphere Model Intercomparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In other words, by excluding interactions with the ocean, we could focus more closely on analyzing the contributions of clouds and atmospheric variables when determining the factors influencing TUCRE. However, the variability of TUC feedback estimated over longer terms may differ from those estimated over shorter terms (such as monthly data) as in this study 32 . Therefore, we suggest further research to consider such aspects in understanding TUCRE and the factors determining it.…”
Section: Discussionmentioning
confidence: 56%
“…In other words, by excluding interactions with the ocean, we could focus more closely on analyzing the contributions of clouds and atmospheric variables when determining the factors influencing TUCRE. However, the variability of TUC feedback estimated over longer terms may differ from those estimated over shorter terms (such as monthly data) as in this study 32 . Therefore, we suggest further research to consider such aspects in understanding TUCRE and the factors determining it.…”
Section: Discussionmentioning
confidence: 56%
“…In particular, these satellite-based decomposition of cloud feedbacks can be used to evaluate the ability of GCMs to simulate the interannual cloud feedback if compared in an equivalent fashion, that is, using the relevant satellite simulator, the same time period, and the same analysis methods. Direct comparisons between GCMs and satellite observations can reveal shortcomings in the representation of certain cloud regimes (Chao et al, 2024). It is therefore important that modeling centers continue to or begin to adopt satellite simulators in their simulations and make their output publicly accessible.…”
Section: Discussionmentioning
confidence: 99%
“…The results presented herein are relevant to both approaches of constraining the cloud feedback: we apply satellite remote sensing observations directly to infer the interannual cloud feedback using a novel technique as a step toward indirectly improving GCMs at the process level. Although the interannual cloud feedback inferred from the novel technique employed here relates to short timescale processes that may not necessarily correspond to the long-term cloud feedback inferred from GCMs (Chao et al, 2024), many of the cloud processes that cause uncertainties in the long-term cloud feedback are observable short-term responses. Indeed, it has been shown that interannual and long-term cloud feedbacks are well-correlated across GCMs (Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%